Binder characterization and performance of warm stone mastic asphalt mixture - Arafat Yero, Suleiman (2012)
The conventional stone mastic asphalt (SMA) is normally produced at high temperature (180oC) that consumes fuel, increases cost, and generates heat with emissions of green house gases. This study investigated the potential of producing stone mastic asphalt at lower temperature (130oC) termed as warm stone mastic asphalt (WSMA) against the normal high mixing temperature. Three grades of bitumen 80/100, 60/70 and PG 76-22 were investigated. A long chain aliphatic hydrocarbon Sasobit wax (SW) was used as an additive to reduce the mixing temperature. The Sasobit wax was incorporated at 0.5%, 1%, 1.5%, 2%, 2.5% and 3% of bitumen content. The empirical tests were conducted on 105 samples of the three binder types, which include penetration test at 10oC and 25oC. Softening point test, dynamic viscosity (DV) at 135oC and kinematic viscosity (KV) at 60oC were conducted to determine the penetration index (PI) and penetration viscosity number (PVN). The results indicate the modified bitumen has better resistance to temperature susceptibility with the additive and better resistance to rutting as it decreases the viscosity of the binder at high temperatures and produces high stiffness modulus as compared to the base bitumen. The study also investigated 126 samples for rheology test of the bitumen using the rolling thin film oven test (RTFOT), pressure aging vessel (PAV), and dynamic shear rheometer (DSR). The results from these tests at high test temperature indicate higher complex shear modulus (G*/sind) with low phase angle (increase stiffness) for aged modified binders indicating better resistance to rutting damage, while at low test temperature they exhibit low complex modulus with high phase angle (decrease stiffness) indicating better resistance to fatigue. The testing on the compatibility and morphology of the modified binders using the scanning electron microscopy test (SEM) were also conducted. The results show the homogeneity of the binder with Sasobit as is completely soluble in the binder with no agglomeration. The study investigated the effect of the warm asphalt additive on the binder aging using Fourier transformation infrared test (FTIR). The results show an insignificant impact on the binder aging. The study prepared and investigated 225 samples of SMA14 and WSMA14 mixtures using the Marshall mix design. The flow and stability tests conducted on the WSMA mixtures show values higher than the minimum JKR/SPJ/2008-S4 specification for SMA in Malaysia with less than 2.5% Sasobit in the three binder sourced investigated. The study recommends up to 2% Sasobit for PEN 80/100, up to 1.5% for PEN 60/70 and 1% for PG 76-22. Based on the penetration test conducted, the two modified PEN bitumen can be categorized as PG 76-22. Also the performance test on the asphalt mix with Sasobit that include rutting and resilient modulus test indicated resistance to rutting damage. Thus, it can be concluded that the Sasobit wax improves bitumen performance, decreases asphalt production temperatures and is feasible to be used in the production of WSMA.